Review of Access Policy in the Credit Tranches and Under the Extended Fund Facility and the Poverty Reduction and Growth Facility, and Exceptional Access Policy. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2008)
This paper reviews the Fund's access policy under its main financing facilities in the General Resources Account (GRA) and under the Poverty Reduction and Growth Facility (PRGF). It responds to the Board's request for a periodic review of the access policy, that is, the rules and practices that govern the amount of financing the Fund makes available to its members.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet